Kecerdasan Budaya Dalam Proses Pencegahan dan Resolusi Konflik di Kabupaten Sumbawa - Amrullah Amrullah; Muslim Muslim; Sri Nurhidayati; wiwi Noviati; M Salahuddin (Prodi Manajemen Fakultas Ekonomi dan Bisnis Universitas Islam Raden Rahmat Malang, 2018)
The Sumbawa community is known as a heterogeneous society, inhabited by people of various ethnic, ethnic, linguistic and religious backgrounds with consequences for different customs and systems of life. This condition is one of the main capital that if misused will be able to negatively impact the emergence of sentiments and communal conflicts that can damage the system of social life. The process of mediation, arbitration and negotiation is one of the approaches used in resolving conflicts over the years. While there are many other methods or approaches that are considered quite effective and sometimes forgotten in the approach of prevention and conflict resolution is through the approach of Cultural Intelligence. So this research, trying to raise the urgency issue of the cultural intelligence in preventing and resolving the conflict. The problems raised in this study are: 1). What factors can cause conflict in society ?, 2). Who actor that acts as a structural, accelerator and trigger or trigger in the conflict ?, 3). What approaches have been used in preventing and resolving the conflict in society by the government ?, 4). Why is cultural intelligence so important in preventing and resolving the conflict? The research method in this research is descriptive-qualitative. The aim of this research that the disclosure of the phenomenon in the research location freely possible to get maximum results because the data is valid and can be accounted scientifically and rationally.Data collection techniques that is used in this research are techniques of observation, interview and documentation. Data analysis techniques start from the process of data collection, data reduction, data presentation, and data validity consisting of credibility, transferability, dependability and comfirmability. The result of the research, that the occurrence of conflict in Sumbawa Regency caused by Structural factor, Accelerator and Trigger (SAT) conflict, for example: there is still and strong Political Memory in Society. As well as the importance of Cultural Intelligence in preventing and resolving of conflicts, as all aspects of Cultural Intelligence such as: Knowledge, Strategy, Motivation and Behavior have the relevance and ability to encourage and create a safe, peaceful and harmonious atmosphere in society as long as society can and able to internalize these values ​​in everyday life. Keywords: Cultural Intelligence, Prevention, Resolution, Conflict